2021
DOI: 10.1371/journal.pone.0254132
|View full text |Cite
|
Sign up to set email alerts
|

Dialogic gathering of films. Promoting meaningful online interactions during COVID-19 confinement

Abstract: A broad body of scientific literature exists on the effects that COVID-19 related confinement has had on the population: mental health problems, isolation, and problems concerning cohesion and employment, among others. However, there is a gap in the literature on the actions that reverse some of the effects generated during lockdown. This article collects the results of a study conducted with 53 people participating in a dialogic gathering of films (DGF) that was held online during two months of confinement. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…They also use the language of desire to extol the traditional Bond model by calling him seductive, charming, elegant, mixed with descriptions such as philandering and cold, thus making the latter characteristics attractive. In this framework, further research could also focus on how the dialogue about films between a diversity of people (Padrós-Cuxart et al, 2021) may or may not influence the language of desire as has been observed in other dialogic gatherings (Rodrigues de López de Aguileta et al, 2020;Salceda et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They also use the language of desire to extol the traditional Bond model by calling him seductive, charming, elegant, mixed with descriptions such as philandering and cold, thus making the latter characteristics attractive. In this framework, further research could also focus on how the dialogue about films between a diversity of people (Padrós-Cuxart et al, 2021) may or may not influence the language of desire as has been observed in other dialogic gatherings (Rodrigues de López de Aguileta et al, 2020;Salceda et al, 2020).…”
Section: Discussionmentioning
confidence: 99%